Articulador del Parque Central Bavaria (2017)
"The project arises from the need to connect the public space of the Parque Central Bavaria together with the neighborhood Teusaquillo, it is proposed to articulate them to form a route that shows the history of the urban development of Bogota. For this case the types of continuity between the sectors of the International Center and the neighborhood Teusaquillo were studied, projecting the line of high meter a future on the Caracas Avenue." -- Tomado del Formato de Documento de Grado.